Prevalence of Moderate to Severe Periodontitis in an 18-19th Century Sample-St. Bride's Lower Churchyard (London, UK) - Ruqayah Al-Mutairi; Helen Liversidge; David Geoffrey Gillam (MDPI AG, 2022)
The aim of the study was to determine the prevalence of moderate to severe periodontitis in 18-19th century skulls in the St Bride's Lower Churchyard in London, UK. Materials and methods: A total of 105 adult skulls (66 M: F 39) from the Museum of London collection were examined for evidence of dental disease. The primary method was to measure the presence of moderate to severe periodontitis. Other dental pathologies were recorded such as tooth wear, calculus, and caries. Results: Overall, the prevalence of moderate to severe periodontitis in the sample was 21-24%. Males were observed to be more susceptible to periodontal disease than females. The severity of bone loss in the skull collection also increased with age. There was no significant difference in the amount of calculus deposition when comparing either age or sex. A total of 14% of the individuals in the sample showed signs of smoking. Conclusion: The results of the study indicated that the prevalence of moderate to severe periodontitis in an 18-19th century skull sample was 21-24%, which was higher than in previous studies. This may be due to the lack of basic personal mouth care and professional dental treatment as well as known risk factors such as smoking, stress, low socioeconomic status, and malnutrition.